Respuesta :
solve for r.
6qr+7rs−2st=−9
Add 2st to both sides.
6qr+7rs−2st+2st=−9+2st
6qr+7rs=2st−9
Factor out variable r.
r(6q+7s)=2st−9
Divide both sides by 6q+7s.
r(6q+7s) / 6q+7s = 2st−9 / 6q+7s
r = 2st−9 / 6q+7s
6qr+7rs−2st=−9
Add 2st to both sides.
6qr+7rs−2st+2st=−9+2st
6qr+7rs=2st−9
Factor out variable r.
r(6q+7s)=2st−9
Divide both sides by 6q+7s.
r(6q+7s) / 6q+7s = 2st−9 / 6q+7s
r = 2st−9 / 6q+7s
6qr + 7rs - 2st = -9
6qr + 7rs = -9 + 2st
r ( 6q + 7s ) = -9 + 2st
r = -9 + 2st / 6q + 7s Ans
6qr + 7rs = -9 + 2st
r ( 6q + 7s ) = -9 + 2st
r = -9 + 2st / 6q + 7s Ans